PENGOLAHAN DAN PELUANG PENGEMBANGAN PRODUK PANGAN BERBASIS MINYAK SAWIT DI INDONESIA / Processing and Palm Oil-Based Food Product Development Opportunities In Indonesia - Hasrul Abdi Hasibuan (Jurnal Penelitian dan Pengembangan Pertanian, 2021)
Palm oil is produced from the mesocarp part of the oil palm fruit (Elaeis guineensis Jacq.), contains balanced saturated fatty acids (47.8-55.2%) and unsaturated fatty acids (43.1-53.8%), and is semi-solid at room temperature with a melting point of 33.0-39.0 °C. About 80%, palm oil is applied to food products. In food products, palm oil needs to be purified through a refining process to remove free fatty acids, water, and impurities. Palm oil can be fractionated based on differences in melting points to produce palm olein fraction and palm stearin fraction with yields of about 70- 80% and 20-30%, respectively. Food products produced from palm oil and its fractions include cooking oil, vanaspati, shortening, margarine, cocoa butter equivalent, and human milk fat substitute. These food products are produced by modifying the physicochemical characteristics of palm oil and its fractions through blending, hydrogenation, and interesterification processes. The challenge for the palm oil industry in the future is to produce products that are low in contaminants such as 3- monochloropropane-1,2-diol and glycidyl esters, trans-fat free, and products that have high functional and nutritional value, such as structured lipids. Improving the quality and developing diversification of palm oil-based food products will encourage the sustainability of the palm oil industry in Indonesia.Keywords: Palm oil, processing, palm oil, food product AbstrakMinyak sawit dihasilkan dari bagian mesokarp buah tanaman kelapa sawit (Elaeis guineensis Jacq.), mengandung asam lemak jenuh (47,8-55,2%) dan asam lemak tak jenuh (43.1-53,8%) seimbang, dan berbentuk semi padat pada suhu ruang dengan titik leleh sebesar 33,0-39,0°C. Sekitar 80%, minyak sawit diaplikasikan untuk produk pangan. Pada produk pangan, minyak sawit perlu dimurnikan melalui proses rafinasi untuk menghilangkan asam lemak bebas, air dan kotoran. Minyak sawit dapat difraksinasi berdasarkan perbedaan titik leleh untuk menghasilkan fraksi olein sawit dan fraksi stearin sawit dengan rendemen masing-masing sekitar 70- 80% dan 20-30%. Produk pangan yang dapat dihasilkan dari minyak sawit dan fraksi-fraksinya meliputi minyak goreng, vanaspati, shortening, margarin, cocoa butter equivalent dan human milk fat substitute. Produk-produk pangan tersebut dihasilkan dengan memodifikasi karakteristik sifat fisikokimia minyak sawit dan fraksi-fraksinya melalui proses pencampuran (blending), hidrogenasi, dan interesterifikasi. Tantangan industri minyak sawit ke depan adalah menghasilkan produk rendah kontaminan seperti 3-monokloropropana-1,2-diol dan glisidil ester, bebas lemak trans, dan produk yang memiliki nilai fungsional dan nutrisi tinggi seperti lipida terstruktur. Dengan dilakukannya peningkatan kualitas dan pengembangan diversifikasi produk pangan berbasis minyak sawit akan mendorong keberlanjutan industri kelapa sawit di Indonesia.Kata kunci: Kelapa sawit, pengolahan, minyak sawit, produk pangan